Lean accounting – as a future accounting system - M.V. Koryagin; M.Yu. Chik (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The historical development of lean accounting is researched. The comparison of lean accounting and accounting is carried out. The article determines the lean accounting basic principles, which are the basis for the selection of main ten steps of upgrading to the system of lean accounting: the evaluation of the current situation and the expected development prospects of the enterprise; the development of the principles of implementing lean accounting; the determining the production parameters and methodology of the economic model construction; the organization of lean manufacturing environment and reducing most of the stock; the determining the flow of value creation; the rejection of variable accounting and reverse cancellation of all labor costs and the cost of materials; the rejection of tracking stocks and assign of the costs directly to the costs of sales when occurred; the definition of client-targeted spending; the relationship with suppliers and automation of the accounts payable; the relationship with customers and automation of the payments received.